From Tukhmah to Wamḍah: The Literary Forum at the University of Aleppo, Its Critical Enterprise, and the New Poetics of Minimalism. - Behar, Daniel (Journal of Arabic Literature, 2022)
This essay presents a synoptic view and a critical synthesis of the activity of the Literary Forum at the University of Aleppo (1980–1986) with the aim of putting Aleppo on the map of modern Arabic literature. Serving as an intensive laboratory for literary and meta-literary production under political duress, the Forum is situated at a confluence of global cultural currents as well as at a turning point in the history of the Arabic prose poem. The Forum members devised literary strategies for coping with the deterioration of their city's cultures while working within both an Arabic tradition of modernity and a global space of intellectual engagement. Well into the twenty-first century, the Forum's legacies continue to shape the moral stances of poets facing disaster at home and the precariousness of statelessness abroad, and extend into forms of civilian solidarity and collective organizing.